STRATEGI PENDANAAN PENDIDIKAN MELALUI ZAKAT INFAK SEDEKAH (ZIS) KASUS PANTI ASUHAN MIFTAHUNNAJAH - Fifin Candra Arifa (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2013)
Miftahunnajah’s orphanage had ZIS (Zakat, Infak, Sedekah) funds in the used to daily needs and operational costs homecare (home funds), tithe (zakat) is also used as a strategy for education funding for students who are unable to foster students (poor, poorness, fatherless orphans, and orphans). Education programs in the Miftahunnajah’s orphanage has two educational programs for students in the orphanage which is formal and non-formal education. Formal education there are 6 students are studies in Islamic High School Lab of UIN and 69 students again studies at Islamic Senior High School Lab of UIN and Senior High School of Babarsari. As for as non formal education Miftahunnajah’s Miftahunnajah’s orphanage has four programs, namely tahfiz al-Qur’an, the religious book, entrepreneurial and school education programs.